Transgressive gaze: representations of patriarchy in two films by Latin American female directors - De la Barra Van Treek, Erika; Carbone Bruna, Soffia (Árboles y Rizomas, 2024)
This paper analyses the films Camila by María Luisa Bemberg (1984) and La Niña Santa by Lucrecia Martel (2003) from a feminist perspective, emphasizing the problem of the gaze. The article contextualizes the cultural and social spheres in which both films emerged and defines the term gaze in film language, relying mainly on Mulvey’s theory (1989) and some later developments by feminist theorists. A comparative analysis addresses the narratological and aesthetic differences of both filmmakers. Camila uses a more classical and melodramatic approach, while La Niña Santa adopts a more elliptical and sensorial style. These differences are manifested in the way the protagonists exercise their gaze. In Camila, the protagonist defies social norms by pursuing her freedom and autonomy, while in La Niña Santa, Amalia assumes an ambiguous gaze that navigates between innocence and desire. The findings reveal that despite these formal differences, both films present a feminist gaze that reconfigures the traditional role of women as passive objects of desire, giving them the capacity to observe and actively transform the world, challenging patriarchal structures.
Keywords: gaze; patriarchy; subversion; desire; stereotype